Poverty and Economic Growth Against the Level of Human Development Index in Mamuju Regency - Asdar; Abdul Rajab; Muhammad Marwan (Jurnal Actual Organization Of Economic, 2023)
The Human Development Index in Mamuju Regency has increased every year from the last seven years and data from the Central Bureau of Statistics (BPS) for Mamuju Regency in 2022 with a score of (68.88%), this value is a high value of the Human Development Index (IPM) ) in Mamuju Regency compared to several areas in West Sulawesi Province. In Mamuju Regency, in the last seven years, poverty and economic growth have fluctuated every year. Based on data obtained from the Central Bureau of Statistics, the Human Development Index (IPM) in Mamuju Regency has increased significantly from year to year, but there are still several social and economic problems, especially the problem of poverty that needs to be prioritized in Mamuju Regency, so that all can receive a decent standard of living. This research was conducted in Mamuju Regency. The research method used is a quantitative method, namely a research method in which the presentation of data is dominated in the form of numbers using secondary data obtained from the office of the Central Bureau of Statistics of Mamuju Regency. Using documentation data collection methods and field studies. Data analysis methods Multiple linear regression, t test, F test, Coefficient of Determination. The results of the T test revealed that the variables of Poverty and Economic Growth had a partial effect on the Human Development Index in Mamuju Regency. The results of the F test show that the variables Poverty and Economic Growth simultaneously influence the Human Development Index in Mamuju Regency.